Preliminary Cbservations on the Lunar and Tidal Influences on the Catches of Mullets (Family- Mugilidae) by Gillnet in the Estuary of Mangalore, Karnataka - Ahmed, Sarifuddin; D.S., Sheshappa (Fishery Technology, 2025)
The paper deals with the lunar and tidal influences on the catches of mullets (Family-Mugilidae) by gillnets in the estuarine waters of Mangalore. The landings during full- moon and new moon phases and during different quarters of the lunar month for a period from October 1990 to April 1991 are discussed.